Amphiphilic block versus random copolymer nanoparticles with reactive oxygen species responsiveness as berberine vehicles. Issue 13 (21st May 2021) - Guo, Honglei; Guo, Qianqian; Lan, Tianyu; Luo, Yongjun; Pan, Xiuhao; Yao, Yifang; Li, Yafei; Feng, Ya; Liu, Yujia; Tao, Ling; Shen, Xiangchun
Abstract: A series of amphiphilic block and random copolymers based on phenylboronic acid pinacol ester were synthesized via reversible addition–fragmentation chain transfer polymerization. The obtained copolymers can self-assemble in aqueous solution into stable block copolymer nanoparticles and random nanoparticles with sizes of 116.1–158.6 and 126.3–187.0 nm, respectively. All nanoparticles showed hydrogen peroxide (H2 O2 ) sensitivity, and the random copolymer nanoparticles presented faster responsiveness to H2 O2 than did those derived from block copolymers. Berberine (BBR) can be effectively encapsulated into block and random copolymer nanoparticles with loading capacity of 7.6%–9.1% and 7.3%–8.9%, respectively. The BBR release can be controlled in an H2 O2 medium. For the random copolymer nanoparticles, the release rate of BBR was faster and the cumulative release amounts in response to H2 O2 were higher over 48 h. The BBR cumulative release amount in the H2 O2 medium for the block and random copolymer nanoparticles was 62.2%–70.2% and 68.6%–80.4%, respectively. Moreover, good biocompatibility was observed for the BBR-loaded block and random copolymer nanoparticles. BBR and BBR-loaded nanoparticles can improve Glut4 translocation to the cell membrane and promote glucose transport into cells. BBR-loaded nanoparticles can decrease the blood glucose levels in diabetic rats over 15 days. These results imply that the different chain formulation of block and random copolymers affects the H2 O2 responsiveness and that the two kinds of nanoparticles exhibit potential application as novel vehicles for BBR delivery to regulate blood glucose levels. GRAPHICAL ABSTRACT: UF0001